PENGARUH MOTIVASI TERHADAP LOYALITAS KERJA KARYAW - Simbolon, Hotma BR; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
PT. Agung Automall Pekanbaru Branch is one of the first Toyota dealer in Pekanbaru is located at Jl. Dr Sutomo 13 Pekanbaru. PT. Agung Automall Pekanbaru Branch requires employees to have the ability and professional services to form PT. Agung Automall be a strong marketing organization. Quality and service excellence is the goal of every employee to make a loyal customer.Data were obtained from questionnaires and subsequently processed to then tested using statistical analysis such as a simple linear regression analysis, t test, and correlation analysis and determination using SPSS 17.The results showed that the t-test of hypothesis testing results tcount 8.233> 1.998 and sig ttable 0.000 <0.05. This suggests that a significant effect on employee motivation. The magnitude of the effect of work environment on employee performance on PT.Agung Automall.Keywords: Motivation, Work Loyalty, PT.Agung Automall